2008
DOI: 10.1161/strokeaha.107.504993
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antithrombotic Therapy Increases Severe Bleeding Events in Patients With Stroke and Cardiovascular Disease

Abstract: Background and Purpose-We sought to determine the incidence and severity of bleeding events in patients with stroke and cardiovascular diseases who were taking oral antithrombotic agents in Japan, where the incidence of hemorrhagic stroke is higher than in Western countries. Methods-A prospective, multicenter, observational study was conducted; 4009 patients who were taking oral antithrombotic agents for stroke and cardiovascular diseases were enrolled. The patients were classified into 4 groups according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 234 publications
(123 citation statements)
references
References 41 publications
10
108
2
3
Order By: Relevance
“…Subjects who took other combinations of medications (n 57), including 23 subjects who took various combinations of antiplatelet and anticoagulant agents, also had a relatively high number of bleeding events. These findings are consistent with the results of previous studies, which showed that the concomitant administration of antiplatelet and anticoagulant agents was associated with a relatively high risk of bleeding complications [28][29][30] . From the results of our study, however, we were unable to conclude that the combined use of antiplatelet and anticoagulant agents was an independent predictor of bleeding events.…”
Section: Discussionsupporting
confidence: 93%
“…Subjects who took other combinations of medications (n 57), including 23 subjects who took various combinations of antiplatelet and anticoagulant agents, also had a relatively high number of bleeding events. These findings are consistent with the results of previous studies, which showed that the concomitant administration of antiplatelet and anticoagulant agents was associated with a relatively high risk of bleeding complications [28][29][30] . From the results of our study, however, we were unable to conclude that the combined use of antiplatelet and anticoagulant agents was an independent predictor of bleeding events.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, a single antiplatelet agent was the most common therapy in the cerebral angiography group, which included a large number of ischemic stroke patients. This is, however, an expected result, since multiple antiplatelet agents or the coadministration of antiplatelet agents and anticoagulants leads to an increase in intracranial bleeding and life-threatening severe bleeding in patients with a history of cerebrovascular disorders (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…29 Lately, antiplatelet treatment with hypertension has been associated with the occurrence of intracranial hemorrhages. 29 Even if hemorrhagic complications occur after stent placement, their incidence is low, about 2.2%; no intraparenchymal hemorrhage has been described remote from an aneurysm treated with stents. Therefore, the FD probably has a specific mechanism that may lead to intraparenchymal hemorrhage and that could be amplified by the antiplatelet regimen.…”
Section: Antiplatelet Regimen Fd and Stentmentioning
confidence: 99%